A New Upper Bound for A-1 of a Strictly α-Diagonally Dominant M-Matrix. (26th December 2013) - Yang, Zhanshan; Zheng, Bing; Liu, Xilan
Abstract : A new upper bound forA - 1 of a real strictly diagonally dominantM -matrixA is present, and a new lower bound of the smallest eigenvalueλ min A ofA is given, which improved the results in the literature. Furthermore, an upper bound forA - 1 of a real strictlyα -diagonally dominantM -matrix is shown.